The Impact of Modern Technologies and Methods on the Management of Key Logistics Activities - Nikola Macura; Marija Pavličević; Tijana Marić; Milosav Anđelić; Nikica Popović (Anali Ekonomskog fakulteta u Subotici, 2026)
Purpose: This paper examines the impact of modern technologies and methods on the management of keylogistics activities, with a particular focus on warehousing and transportation. The aim is to assess howinnovative logistics solutions contribute to improving the speed, efficiency, safety, and sustainability of logisticsoperations.Methodology: The study is based on a review of relevant academic and professional literature, supported bycase studies of leading global companies, including Amazon, Alibaba, JD.com, Walmart, DHL, UPS, IKEA, andAlphabet. The analysis covers modern warehousing and transportation technologies, including robotics,automation, artificial intelligence, drones, and Hyperloop solutions.Findings: The findings indicate that the adoption of modern logistics technologies significantly improvesoperational efficiency, reduces logistics costs, accelerates order processing and delivery, enhances warehousespace utilization, and contributes to more sustainable logistics systems. At the same time, successfulimplementation requires substantial initial investments, workforce upskilling, and organizational adaptation.Originality/value: The paper provides an integrated overview of the most important contemporary logisticstechnologies and methods by examining their practical implementation in leading global companies, highlightingtheir advantages, limitations, and implications for the future development of logistics systems.Practical implications: The findings may assist logistics managers and decision-makers in selecting andimplementing modern logistics solutions to improve competitiveness, service quality, and operational efficiency.Limitations: The paper is based on a literature review and case study analysis rather than empirical research.Consequently, the conclusions represent a synthesis of existing knowledge and provide a foundation for futureempirical studies.